CHANGES OF COLOR AND P-KAROTEN RATE IN THE UBI.JALAR (IPOMEA BATATAS, L) FLOWS BLEACHING - Regina Tutik Padmaningrum; M. Pranjoto Utomo (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2007)
he researh to stuJlythe influence of the kinds and the concentrations of bleach solution to the co1lientof fJharoten and the color ofjaw a sweet potato flour has been done. Yellowjawa sweet potato was used in this reseach. This reseon:h was a descripstive qualitative research. The subject of the researdt was jawa sweet potato and the object was jawa sweet potato flourquantities including the content of fi-charotenand the color of theflour.. TIre independen: variables were the kinds .and the concentrations of bleach solution. and the dependent variableswere the con/ell!offJ-charoten ami.the color ofjawa sweet potato flour. In 1.00% bleach solllliDn. the costen: of fi-charoten with sodium sulfite, sodium bisulfite. Co(OHJ!l. ascorbic acid were: 2.18985,1.40835, 2.25795 and 0.78315 mgllOO grams flour respectively. In1.00% bleach solution. the color of soaked jawa sweet potato flour in sodium sulfite, sodium bisulfite,. Ca(OH);]ascorbic acid were: red (R= 0.3) =yellow (Y = 0.7). red (R = O.2)-yeJlow (Y = 0.5), red (R = 0.5)-yellow(Y= 1.0)andred(R=0.1)-yeHow(R = 1.2) respectively. Theresearch showed that the concentration of bleach solution influencedsignificantly the content of fJ-cIwroten and the color of jawa sweet potato flour. The concentration ofbead: solution tat yielded the bigest content offJ-charotenwas LOW